(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article deals with modern issues related to the teaching of socio-humanitarian disciplines of economic orientation in technical institutions. It was determined that the main problems in this aspect are students’ lack of knowledge in these disciplines, which lowers the level of their professional education. It has been studied that the importance of social and humanitarian disciplines lies in the development of soft skills, which are no less important than hard skills in the modern economy. It is substantiated that in order to improve the teaching of socio-humanitarian disciplines of economic orientation in technical institutions, it is necessary to take into account the specifics of professional training and university studies. It is proposed to use interactive teaching methods, such as role-playing games and discussions, which ensure an increase in interest in the study of socio-humanitarian disciplines of the economic direction. It has been proven that the teaching of social and humanitarian disciplines is an important element of economic education in technical institutions, which helps students develop the necessary soft skills for further professional activities. In this aspect, it is necessary to pay special attention to the fact that teachers of socio-humanitarian disciplines of the economic direction should take into account the peculiarities of the professional needs of students studying in technical sciences programs. For example, the teaching of socio-humanitarian disciplines of economic direction can be more effective if it focuses on specific areas that are related to the future professional activities of students. In addition, the need for interaction between teachers of socio-humanitarian disciplines of economic direction and teachers of technical disciplines acquires special importance. Such cooperation can contribute to a more complete coverage of the professional needs of students and ensure the integration of their knowledge from various disciplines in accordance with the integral competence of the educational program. Thus, it can be stated that currently the importance of social and humanitarian disciplines in the economic education of students of technical specialties is growing significantly, which leads to the need to eliminate the problems that arise during their teaching. Solving these problems requires the practical application of various teaching methods that can make the teaching of socio-humanitarian disciplines of the economic direction more effective, and also emphasize the importance of interaction between various components of educational programs.